Peranan UPT Dinas Pasar Dalam Melakukan Pemungutan Retribusi Di Lingkungan Pasar Segiri Kota Samarinda - Hasrina Wati; Nainuri Suhadi (Yuriska: Jurnal Ilmiah Hukum, 2020)
This study aims to determine the role of the Market Service UPT in collecting retribution in the Segiri Market Area of Samarinda City in Review of Samarinda City Regulation Number 2 of 2016 concerning Amendment to Regional Regulation Number 13 of 2011 concerning Public Service Retribution and Market Service actions against money withdrawal carried out by thug persons to traders who illegal sales outside the Segiri Market area of Samarinda City. This research is an empirical legal research that comes from primary legal material and secondary legal material. The results showed that the role of the Market Service in collecting levy in the Segiri Market Area of Samarinda City (reviewed from the Regional Regulation of Samarinda City Number 2 of 2016 concerning Amendment to Regional Regulation Number 13 of 2011 concerning Public Service Retribution), namely three roles, first giving direction, provide supervision and provide guidance. Whereas the actions of the Market Service UPT against money withdrawals made by individual thug to traders who sell illegal outside the Segiri Market area of Samarinda City are divided into two, the first action of the Segiri Market Service UPT against the thug includes conducting thug raids and controlling the land gangster extortion, then secondly, the action of the Segiri Market Service UPT against illegal traders, which includes the provision of sanctions, enforcement, confiscation of merchandise.